Powieści Anny Mostowskiej – ponowne odczytanie - Urbańska, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Mostowska`s novel had no editon since it`s first publication in the first decade of XIX century. For years her literary output was ignored and depreciated. Undoubtely in spite of some flaws, Mostowska` s literary output includes didactic value, innovatory current and tendency. Mostowska was one from the first woman writers. She engaged herself in cultural and literary life, watched over publication of her works. The premise of modern editing Mostowska`s novel is not only to allow reading after two hundred years of break, in the optimum editorial form, but also to show Mostowska`s achievements in a new light. Contemporary edition is an attempt to re‑read and objectify the clerical image of this author. At the beginning of the edition appeared belief or argument that language fault of author should not prevent the critical edition, especially when we are dealing in the artistic achievements, which was not published outside the first edition ever.